Mitochondrial Utilization of Competing Fuels Is Altered in Insulin Resistant Skeletal Muscle of Non-obese Rats (Goto-Kakizaki) - Lai, Nicola; Fealy, Ciarán E.; Kummitha, Chinna M.; Cabras, Silvia; Kirwan, John P.; Hoppel, Charles L. (Frontiers in Physiology, 2020)
Aim: Insulin-resistant skeletal muscle is characterized by metabolic inflexibility with associated alterations in substrate selection, mediated by peroxisome-proliferator activated receptor delta (PPARdelta. Although it is established that PPARdelta contributes to the alteration of energy metabolism, it is not clear whether it plays a role in mitochondrial fuel competition. While nutrient overload may impair metabolic flexibility by fuel congestion within mitochondria, in absence of obesity defects at a mitochondrial level have not yet been excluded. We sought to determine whether reduced PPAR content in insulin-resistant rat skeletal muscle of a non-obese rat model of T2DM (Goto-Kakizaki, GK) ameliorate the inhibitory effect of fatty acid (i.e. palmitoylcarnitine) on mitochondrial carbohydrate oxidization (i.e. pyruvate) in muscle fibers. Methods: Bioenergetic function was characterized in oxidative soleus (S) and glycolytic white gastrocnemius (WG) muscles with measurement of respiration rates in permeabilized fibers in the presence of complex I, II, IV and fatty acid substrates. Mitochondrial content was measured by citrate synthase (CS) and succinate dehydrogenase activity (SDH). Western blot was used to determine protein expression of PPARdelta, PDK isoform 2 and 4. Results: CS and SDH activity, key markers of mitochondrial content, were reduced by 10-30% in diabetic vs control, and the effect was evident in both oxidative and glycolytic muscles. PPARdelta(p<0.01), PDK2 (p<0.01), and PDK4 (p=0.06) protein content was reduced in GK animals compared to Wistar rats (N=6 per group). Ex vivo respiration rates in permeabilized muscle fibers determined in the presence of complex I, II, IV and fatty acid substrates, suggested unaltered mitochondrial bioenergetic function in T2DM muscle. Respiration in the presence of pyruvate was higher compared to palmitoylcarnitine in both animal groups and fiber types. Moreover, respiration rates in the presence of both palmitoylcarnitine and pyruvate were reduced by 25±6% (S), 37±6% (WG) and 63±6% (S), 57±8% (WG) compared to pyruvate for both controls and GK, respectively. The inhibitory effect of palmitoylcarnitine on respiration was significantly greater in GK than controls (p<10-3). Conclusion: With competing fuels, the presence of fatty acids diminishes mitochondria ability to utilize carbohydrate derived substrates in insulin-resistant muscle despite reduced PPARdelta content.